Will you still want me tomorrow? The dynamics of families' long-term care arrangements - Michelle Sovinsky Goeree; Bridget Hiedemann; Steven Stern (University of Zurich, Department of Economics, 2012)
We estimate dynamic models of elder-care arrangements using data from the Assets and Health Dynamics Among the Oldest Old Survey. We model the use of institutional care, formal home health care, care provided by a child, and care provided by a spouse in the selection of each care arrangement, the primary arrangement, and hours in each arrangement. Our results indicate that both observed heterogeneity and true state dependence play roles in the persistence of care arrangements. We find that positive state dependence (i.e., inertia) dominates caregiver burnout, and that formal care decisions depend on the cost and quality of care.
Keywords: C51; C61; J14; 330; Dynamic Models; Long-Term Care; Home Health Care; Informal Care; Heim; Familienpflege; Vergleich; Burnout; Familie; Dienstleistungsqualität; USA